A Tale of Two Sister Clinics: Comparing the Use of Online Scheduling Tools to Reduce Patient Wait Times - Ku, Seul; Liu, Monica; Rea, Sheridan; Mulumba, Kabungo; Chen, Annabel; Dutta, Ritika; Kakusa, Bina; Caceres, Wendy; Singh, Baldeep; Charon, Mina; Montacute, Tamara (Journal of Student-Run Clinics, 2020)
Background: The Cardinal Free Clinics, Arbor Free Clinic (Arbor) in Menlo Park and Pacific Free Clinic (PFC) in San Jose, are student-run free clinics affiliated with Stanford operating since 1990. Patients are seen on a walk-in basis only, and on average, patients may wait more than an hour to be seen, decreasing patient satisfaction. In this study, we looked at whether we could improve patient wait times by administering a free online self-scheduling tool. Methods: The free version of Acuity Online Scheduling Tool was used to set up 6 online appointment slots for patients at Arbor and 12 at PFC, and walk-in services were provided concurrently. On clinic days, patients with appointments were given priority over walk-ins. Wait times were calculated from time points collected by hand or through the electronic health record system. The Mann Whitney U test was used to compare wait times between patients with and without appointments in each clinic. Results: The total number of patients being seen on a given day and whether or not patients had online appointments were significant determinants of wait times. Patients at Arbor with appointments had a median wait time of 35 minutes (N=46) compared to 60 minutes (N=231) without appointments (p<0.05). At PFC, patients with appointments waited 22 minutes (N=123) compared to 26 minutes (N=193) without appointments (p=0.09). Conclusion: Free online scheduling tools can be customized to significantly decrease patient wait times and spread out patient arrival. Given the lack of resources often available for free clinics, it is important to explore the use of free tools to create a better patient experience.